A new limit of the AdS(5) x S-5 sigma model - Berkovits, Nathan (Springer, 2007)
Using the pure spinor formalism, a quantizable sigma model has been constructed for the superstring in an AdS(5) X S-5 background with manifest PSU(2,2 vertical bar 4) invariance. The PSU(2,2 vertical bar 4) metric g(AB) has both vector components gab and spinor components g, 3, and in the limit where the spinor components g, 3 are taken to infinity, the AdS5 X S5 sigma model reduces to the worldsheet action in a flat background. In this paper, we instead consider the limit where the vector components g(ab) are taken to infinity. In this limit, the AdS5 X S5 sigma model simplifies to a topological A-model constructed from fermionic N=2 superfields whose bosonic components transform like twistor variables. Just as d=3 Chern-Simons theory can be described by the open string sector of a topological A-model, the open string sector of this topological A-model describes d=4 N=4 super-Yang-Mills. These results might be useful for constructing a worldsheet proof of the Maldacena conjecture analogous to the Gopakumar-Vafa-Ooguri worldsheet proof of Chern-Simons/conifold duality.
Keywords: Ads-CFT correspondence; superstrings and heterotic strings; topological strings